Changes in land tenure and agricultural intensification in sub-Saharan Africa - Keijiro Otsuka; Frank Place (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Due to increasing population pressure on limited cultivable land in many parts of sub-Saharan Africa (SSA), farm size has been shrinking, fallow periods have been shortened, and soil fertility has been declining. In accordance with the Boserupian evolutionary theory and the Hayami-Ruttan induced innovation theory, however, investments in land improvements have taken place, which leads to strengthened individual land rights and the intensification of farming systems in many other parts of SSA. Based on the literature review, this paper argues that such evolutionary and spontaneous changes should be supported by means of technology development and dissemination, formalization of land rights, and improvement of access to agricultural markets.
Keywords: 330; population pressure; soil degradation; investments in land improvement; strengthened individual land rights; agricultural intensification